THE INTEGRATION OF EX-CONVICT’S EMPLOYMENT OPPORTUNITIES IN MALAYSIA HOSPITALITY INDUSTRY - Rita Lo; Siti Atikah Rusli; Norhafizatul Akma Hamzah, (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
A custodial sentence has four primary goals: retribution, rehabilitation, deterrence, and incapacitation. This study focuses on the skilled and well-trained ex-convict's recruitment opportunity in the hospitality industry after the prison sentence. The Malaysian prison department has provided various vocational skill training for prisoners during incarceration. This initiative aims to give ex-convicts multiple skills to equip them for a job opportunity and reintegrating into society after their jail sentence. However, even after being released, former inmates who have undergone vocational training in prison may still face challenges when seeking employment opportunities. This study will examine the integration of ex-convict’s employment opportunities in Malaysian hospitality industry. The study distributed 393 survey questionnaires to potential hospitality sector employers in Malaysia to assess their willingness to hire former prisoners. Skill acquisition, formal discipline and behaviourist view were extracted from valid theoretical background follow by the employer’s readiness were used in the study. Regression analysis was conducted to test on the hypotheses, which it revealed behaviourist view directly affected the employer’s readiness to hire ex-convict due to the type of criminal record. The finding revealed that skill acquisition has a significant influence on the hire decision when come to operation related vacancies. There were significant correlations between formal discipline and ex-convict’s recruitment decision. This research aims to develop measures and training for convicts to aid in their reintegration into society. It also aims to foster a better behavioural mindset for societies to provide second chances and accept ex-convicts into their community.